PHYSIOLOGICAL AND SENSORIAL ASPECTS OF PEACH FRUITS cv. Chimarrita DEPENDING ON THE SEASON AND MANAGEMENT OF GREEN PRUNING - Dotto, Marcelo; Pirola, Kelli; Wagner Junior, AmÃ©rico; Radaelli, Juliana Cristina; CorrÃªa Antunes, Luis; Citadin, Idemir (REVISTA DE AGRICULTURA, 2017)
For quality peach production it is necessary to perform the correct management in all processes. The objective of this work was to evaluate the time and the management of performing green pruning on the physiological and sensorial aspects of the peach fruits cv. Chimarrita. The work was conducted in an orchard in Dois Vizinhos (PR), during the 2011/2012 production cycle. The experimental design was a completely randomized 3 x 3 factorial scheme, season x types of pruning with 4 replicates. The seasons of green pruning were in the third, fourth and fifth week before harvest. The pruning techniques of green pruning were with the folding of the branches, pruning with the removal of the branch and control without any type of management related to pruning. Sensorial characteristics of the fruits and physiological of the plants were evaluated. The best fruits were observed with folding of the branches and with greater red coloration of the bark was with the removal of the branches, independent of the time of accomplishment.